Presentation - Equipo Editorial (2014)
In this section, you will find the presentation of the third volume of the Anuario Centro de Investigación y Estudios Políticos. The objectives of this journal are explained, as well as the sections into which it is divided, and thanks are given to certain individuals for their collaboration in making this project possible.